Bird Diets in Urban Environments: The Case of the Asian Glossy Starling, Aplonis panayensis - Nursyafiqah, Shazali; Mohd-Azlan, J.; Andrew Alek, Tuen (Springer International Publishing, 2016)
The Asian Glossy Starling, Aplonis panayensis, is one of the most abundant birds in Kuching City, occupying nooks and cavities of buildings and soiling the walls and fl oors with their droppings. To determine why they are so abundant, we focused on their dietary habits in a study conducted in Dewan Suarah area of Kuching in 2013. A total of 51 fecal samples were collected from the fl oor of Dewan Suarah and examined for dietary fragments. The results showed the diet comprises insects as well as plant parts. The insects are solely from the Order Hymenoptera (70 individuals), whereas the plant parts comprised fi gs (86 %), Vitex sp. (2 %) and unidentifi ed plant materials (12 %). The Hymenopteran identifi ed in fecal samples belong to the family Agaonidae (45 individuals), Formicidae (18 individuals), and Ormyridae (7 individuals). There is a signifi cant difference in frequency occurrence of insects and fruits in the diet of starlings. From the fecal analysis, the insects in the diet of the starlings are mainly from the fi gs they have eaten. The diet of the bird is discussed in relation to the availability of food items in the surrounding areas.